2020
DOI: 10.1002/bit.27547
|View full text |Cite
|
Sign up to set email alerts
|

Strain engineering for high‐level 5‐aminolevulinic acid production in Escherichia coli

Abstract: Herein, we report the development of a microbial bioprocess for high-level production of 5-aminolevulinic acid (5-ALA), a valuable non-proteinogenic amino acid with multiple applications in medical, agricultural, and food industries, using Escherichia coli as a cell factory. We first implemented the Shemin (i.e., C4) pathway for heterologous 5-ALA biosynthesis in E. coli. To reduce, but not to abolish, the carbon flux toward essential tetrapyrrole/porphyrin biosynthesis, we applied clustered regularly interspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…The Shemin/C4 pathway was implemented in E. coli via heterologous expression of hemA from R. sphaeroides in BW∆ ldhA (Miscevic et al 2021 ). The resulting control strain, DMH, was cultivated under aerobic conditions in a batch bioreactor with ~ 30 g L −1 of glycerol as the carbon source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Shemin/C4 pathway was implemented in E. coli via heterologous expression of hemA from R. sphaeroides in BW∆ ldhA (Miscevic et al 2021 ). The resulting control strain, DMH, was cultivated under aerobic conditions in a batch bioreactor with ~ 30 g L −1 of glycerol as the carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic implementation of the Shemin/C4 pathway in BW∆ ldhA was previously described (Miscevic et al 2021 ). Heterologous expression of the hemA gene cloned in the pK184 vector was under the control of the P lac promoter.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, great efforts had been made to construct recombinant E. coli and C. glutamicum by expressing an exogenous 5-ALA synthetase (ALAS) gene in order to improve 5-ALA production via the C4 pathway (Li et al 2014 ; Yang et al 2016 ; Ding et al 2017 ; Chen et al 2020 ; Yu et al 2020 ; Miscevic et al 2021 ). So far, the production of 5-ALA has been significantly improved through fermentation process optimization, pathway engineering or tolerance engineering.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that HemB inhibitors such as levulinic acid (Sasaki et al 1987 ), D-xylose (Lin et al 2009 ) and D-glucose (Lee et al 2003 ) could effectively promote ALA accumulation and more recently, Zhang et al ( 2019 ) replaced the promoter of ALA dehydratase with fliCp to weaken ALA catabolism. In a different type of approach, Su et al ( 2019 ) fine-tuned the expression of hemB with CRISPR interference (CRISPRi) to improve ALA accumulation, while Miscevic et al ( 2021 ) repressed hemB expression by applying CRISPRi to target various sequences in the promoter and ORF regions for achieving the same results. However, to a certain extent, the repression of hemB impaired the growth of cells (Miscevic et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation